2022
DOI: 10.17269/s41997-022-00648-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intention to receive vaccines for bacterial sexually transmitted infections among young HPV-vaccinated Canadian women

Abstract: Objective The aim of this study was to explore the acceptability of bacterial STI vaccines among young HPV-vaccinated Canadian women to inform future vaccine program implementation. Methods A 20-item cross-sectional questionnaire was administered from June 2019 to June 2020 to HPV-vaccinated participants of the pan-Canadian QUEST cohort. Multivariable logistic regression models assessed interest in chlamydia, syphilis, and gonorrhea vaccines using a priori variables and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…However, they were willing to consider the vaccine if it were provided for free or at cheaper prices, which aligns with a previous study conducted in Canada where mothers were moderately willing to get their sons' HPV vaccine for free, but much less willing to pay the out-of-pocket cost [36]. This sentiment is likely common among financially underprivileged parents [37]. Recent studies in Canada, Ghana, Nigeria, and Sweden have underscored that high cost would be a major barrier to being interested in or receiving STI vaccines and that those that require multiple doses or boosters, such as the HPV vaccine, will have greater financial implications for public acceptance of out-of-pocket costs [37][38][39][40].…”
Section: Principal Findingssupporting
confidence: 75%
See 1 more Smart Citation
“…However, they were willing to consider the vaccine if it were provided for free or at cheaper prices, which aligns with a previous study conducted in Canada where mothers were moderately willing to get their sons' HPV vaccine for free, but much less willing to pay the out-of-pocket cost [36]. This sentiment is likely common among financially underprivileged parents [37]. Recent studies in Canada, Ghana, Nigeria, and Sweden have underscored that high cost would be a major barrier to being interested in or receiving STI vaccines and that those that require multiple doses or boosters, such as the HPV vaccine, will have greater financial implications for public acceptance of out-of-pocket costs [37][38][39][40].…”
Section: Principal Findingssupporting
confidence: 75%
“…This sentiment is likely common among financially underprivileged parents [37]. Recent studies in Canada, Ghana, Nigeria, and Sweden have underscored that high cost would be a major barrier to being interested in or receiving STI vaccines and that those that require multiple doses or boosters, such as the HPV vaccine, will have greater financial implications for public acceptance of out-of-pocket costs [37][38][39][40]. A Greek study also found that having a low income was associated with lower HPV vaccination acceptance among mothers for their sons, although income did not influence women's attitudes for themselves and their daughters [41].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Despite the elusive underlying molecular mechanisms, the variability in guidelines, and a questionable cost-effectiveness profile, we consider that screening for bacterial STIs should be encouraged, at least for reproductive-age women harboring cervical HR-HPV or CIN. In the near future, the potential coadministration of the HPV vaccine together with anti-STI vaccines currently under development might emerge as a cost-effective strategy [68]. As for now, the feasibility of HPV status, bacterial STI, and cytology coassessment in vaginal self-sampling material is particularly attractive and potentially more cost-effective [61,69].…”
Section: Discussionmentioning
confidence: 99%